NUMBER OF LEVEL CROSSINGS OF RANDOM ALGEBRAIC POLYNOMIALS - MISHRA, DR.P.K. (IJRDO -JOURNAL OF MATHEMATICS, 2019)
In this paper, we have estimated bounds of the number of level crossings of the random algebraic polynomials where are dependent random variables assuming real values only and following the normal distribution with mean zero and joint density function. There exists an integer n0 and a set E of measure at most such that, for each n>n0 and all not belonging to E, the equations (1.1) satisfying the condition (1.2), have at most roots where α and A are constants. 1991 Mathematics subject classification (Amer. Math. Soc.): 60 B 99.